Postnatal Exposure to Ethanol Increases Its Oral Acceptability to Adolescent Rats. (29th August 2018) - Tang, Joyce; Youngentob, Steven L; Glendinning, John I
Abstract: The aversive flavor of ethanol limits intake by many consumers. We asked whether intermittent consumption of ethanol increases its oral acceptability, using rats as a model system. We focused on adolescent rats because they (like their human counterparts) have a higher risk for alcohol overconsumption than do adult rats following experience with the drug. We measured the impact of ethanol exposure on 1) the oral acceptability of ethanol and surrogates for its bitter (quinine) and sweet (sucrose) flavor components in brief-access lick tests and 2) responses of the glossopharyngeal (GL) taste nerve to oral stimulation with the same chemical stimuli. During the exposure period, the experimental rats had access to chow, water and 10% ethanol every other day for 16 days; the control rats had access to chow and water over the same time period. The experimental rats consumed 7–14 g/day of 10% ethanol across the exposure period. This ethanol consumption significantly increased the oral acceptability of 3%, 6% and 10% ethanol, but had no impact on the oral acceptability of quinine, sucrose or NaCl. The ethanol exposure also diminished responses of the GL nerve to oral stimulation with ethanol, but not quinine, sucrose or NaCl. Taken together, these findings indicate that ethanol consumption increases the oral acceptability of ethanol in adolescent rats and that this increased oral acceptability is mediated, at least in part, by an exposure-induced reduction in responsiveness of the peripheral taste system to ethanol per se, rather than its bitter and sweet flavor components.